Treatment of lupus nephritis and primary glomerulonephritis with enteric-coated mycophenolate sodium - Kitiyakara C. (2014)
Aims: Mycophenolate mofetil is an effective therapy for lupus nephritis (LN) and other glomerulonephritis (GN). However, gastrointestinal (GI) complications can limit its use. Enteric-coated mycophenolate sodium (EC-MPS) has been designed to reduce GI adverse events, but it has not been fully investigated in the treatment of GN. Methods: Patients with LN and primary GN who had received EC-MPS were studied for effects on renal function. Results: 30 subjects (17 LN, 13 primary GN) were studied. ECMPS decreased proteinuria in both LN and GN. In LN, 16 patients had EC-MPS as induction therapy. Of these, 8 patients achieved complete remission (CR), 4 had partial remission (PR) and 1 improved renal function. In primary GN, CR was achieved in 4 out of 5 with minimal change disease, but only 1 did not relapse. PR was achieved in 1 of 4 patients with membranous glomerulopathy, 2 out of 2 patients with focal segmental glomerulosclerosis and 1 out of 2 patients with IgA nephropathy. Infections, anemia and alopecia were observed, but no patient had GI side effects. Conclusions: EC-MPS is effective in LN, but not as effective in primary GN. The risk of GI side effects appears to be low, but other side effects can still occur. © 2008 Dustri-Verlag Dr. K. Feistle.